Publisher Correction: Coupling of ocean redox and animal evolution during the Ediacaran-Cambrian transition - Dan Wang (Nature Portfolio, 2018)
The original version of this Article incorrectly gave the second address in the list of affiliations as “State Key Laboratory of Palaeobiology and Stratigraphy & Center for Excellence in Life and Paleoenvironment, Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, 210008 Nanjing, China”, instead of the correct ‘State Key Laboratory for Mineral Deposits Research, School of Earth Sciences and Engineering, Nanjing University, Nanjing 210023, China”. This has been corrected in both the PDF and HTML versions of the Article.